Pseudogene GTF3AP2 is involved in the regulation of erythroid differentiation - XIA Lan, RONG Yu, XIA Hongkai, MA Yanni, YU Jia (Jichu yixue yu linchuang, 2025)
Objective To investigate the effect of pseudogene GTF3AP2 in erythroid differentiation. Methods The published high-throughput RNA sequencing(RNA-seq) data were analyzed to identify the functional pseudogene GTF3AP2, which may play a role in erythropoiesis. The endogenous expression of GTF3AP2 was inhibited by shRNA in CD34+ hematopoietic stem/progenitor cells to assess the colony-forming ability through colony-forming assay. Flow cytometry analysis was applied to detect changes in the ratio of erythroid/megakaryocytic progenitor cells. Additionally, the role of GTF3AP2 in erythroid differentiation was determined through transcriptome sequencing, which revealed alterations at the cellular and molecular levels following the knockdown of GTF3AP2. Results Compared with the sh-EV group, knockdown of GTF3AP2 resulted in a significant increase in cell expansion, characterized by a significant rise in the number of colony-forming unit erythroid cells(P＜0.001), an increase in the proportion of CD71+CD235a+ erythroid precursors(P＜0.01), and a decrease in the proportion of CD71-CD235a+ mature erythrocytes(P＜0.05). Furthermore, there was a significant reduction in the expression of key erythroid differentiation genes, including KLF1, HBB, GYPA, EPOR and TFRC. Conclusions Knocking down of GTF3AP2 promotes the expansion of erythroid precursor cells and inhibits erythroid maturation, suggesting that GTF3AP2 plays a regulatory role in erythroid differentiation.